An updated floristic map of the world - Liu, Yunpeng; Xu, Xiaoting; Dimitrov, Dimitar; Pellissier, Loic; Borregaard, Michael K.; Shrestha, Nawal; Su, Xiangyan; Luo, Ao; Zimmermann, Niklaus E.; Rahbek, Carsten; Wang, Zhiheng (Nature communications, 2023)
Floristic regions reflect the geographic organization of floras and provide essential tools for biological studies. Previous global floristic regions are generally based on floristic endemism, lacking a phylogenetic consideration that captures floristic evolution. Moreover, the contribution of tectonic dynamics and historical and current climate to the division of floristic regions remains unknown. Here, by integrating global distributions and a phylogeny of 12,664 angiosperm genera, we update global floristic regions and explore their temporal changes. Eight floristic realms and 16 nested sub-realms are identified. The previously-defined Holarctic, Neotropical and Australian realms are recognized, but Paleotropical, Antarctic and Cape realms are not. Most realms have formed since Paleogene. Geographic isolation induced by plate tectonics dominates the formation of floristic realms, while current/historical climate has little contribution. Our study demonstrates the necessity of integrating distributions and phylogenies in regionalizing floristic realms and the interplay of macroevolutionary and paleogeographic processes in shaping regional floras. This study updates the floristic realms of the world by integrating global distributions and mega-phylogenies of 12,664 angiosperm genera. Eight realms and 16 sub-realms are identified, most of which have formed since the Paleogene, and their formation is dominated by geographic isolation induced by plate tectonics rather than current or historical climate.